An investigation of the hand anthropometric database of agricultural workers and integration of the database into tools and protective gear designs - Dewangan, K N; Patel, Thaneswer; Vidhu, K P; Khumukcham, B S; Lusang, I; Sumpi, N; Yudik, L (Work (Reading, Mass.), 2023)
The hand anthropometric data is the baseline for design of hand tools and equipment. This study aimed to generate the hand anthropometric database of male and female agricultural workers and compare it with the hand anthropometric data of other regions of India. The use of collected data is illustrated to design hand tools and protective gear. Hand anthropometric data were collected from 228 male and 198 female agricultural workers of northeast India. A total of 35 hand dimensions, stature and body mass from different tribes in the age group of 18-60 years were precisely measured. Measured data were statistically analysed to study the effects of gender, ethnicity, and age on hand dimensions. Correlation coefficients were determined among hand dimensions and linear regression equations were developed between highly correlated dimensions. The results show that all hand dimensions of the male and female subjects are significantly different (p < 0.01). Most of the hand dimensions were significantly different (p < 0.05) among different tribes for the male subjects. However, less number of hand dimensions were significantly different among tribes for the female subjects. Age of the subjects has significant effects (p < 0.01) on dimensions related to thickness, depth and circumference of fingers. The use of these data in the ergonomic design of hand tools and personal protective gear is illustrated to increase safety and comfort as well as efficiency of operators. There is a difference in the hand dimensions of different tribes of northeast India. This needs to be considered when designing agricultural hand tools and equipment.